2023
DOI: 10.1002/ange.202217701
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Crystal Phase to Form MnGaOx‐Spinel for Highly Efficient Syngas to Light Olefins

Abstract: The oxide-zeolite (OXZEO) catalyst design concept has been demonstrated in an increasing number of studies as an alternative avenue for direct syngas conversion to light olefins. We report that face-centered cubic (FCC) MnGaO x -Spinel gives 40 % CO conversion, 81 % light olefins selectivity, and a 0.17 g g cat À 1 h À 1 spacetime yield of light olefins in combination with SAPO-18. In comparison, solid solution MnGaO x (characterized by Mn-doped hexagonal close-packed (HCP) Ga 2 O 3 ) with a similar chemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…We summed the signals in the reaction temperature range of 395–410 °C (Figure d), in which the oxygenated species of HCOOH and CH 3 OH as well as undesired CO 2 byproducts and the hydrocarbon species of CH 4 and C 3 H 6 were detected. In agreement with the results of in situ DRIFT spectroscopy (Figure a–c), the existence of HCOOH and CH 3 OH oxygenated products further demonstrated that surface active H* was involved in CO activation and the intermediates of HCOO* and CH 3 O* were formed on the surface of Zn 0.10 Cr 0.36 Mn 0.54 oxide …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We summed the signals in the reaction temperature range of 395–410 °C (Figure d), in which the oxygenated species of HCOOH and CH 3 OH as well as undesired CO 2 byproducts and the hydrocarbon species of CH 4 and C 3 H 6 were detected. In agreement with the results of in situ DRIFT spectroscopy (Figure a–c), the existence of HCOOH and CH 3 OH oxygenated products further demonstrated that surface active H* was involved in CO activation and the intermediates of HCOO* and CH 3 O* were formed on the surface of Zn 0.10 Cr 0.36 Mn 0.54 oxide …”
Section: Resultsmentioning
confidence: 99%
“…12,18 Furthermore, Bao et al found when the spinel structure of MnGa 2 O 4 was produced, with more oxygen vacancy sites generated, even higher CO conversion efficiency up to 40% could be achieved. 21 Therefore, deeply understanding the synergistic interactions between catalytic metals and thereby screening the doping metals are of great significance to achieve a high yield of C 2 −C 4 olefins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation